Automated multi-rotor draft survey of large vessels - Usman, Muhammad (UiT Norges arktiske universitet, 2022)
In maritime sector draft survey has a significant importance as it is used to determine many important factors used in maritime transportation. Draft is the vertical displacement from the bottom of the keel (the bottom-most element of a vessel) to the water line (the line of meeting point of hull and the water surface). It is used to measure the minimum water depth for safe navigation of vessel and to evaluate mass of cargo in the vessel by the change in displacement on the draft scale after loading of the cargo in the vessel. Draft measurement of a vessel has a vital role in maritime sector to ensure a safe equilibrium between maximum and minimum cargo that can be loaded in the vessel. Draft survey performed at the time of loading and unloading of cargo (Iron Ore) at the Narvik port to read out draft markings traditionally involved a round trip around the vessel in a small crew boat and it is a time consuming and challenging task specially in darkness (during night), shadows and when difficult to safely reach the crew boat close enough due to anchors and buoys. The goal of this study is to develop an autonomous multi-rotor system that can survey the large vessel to capture all the necessary draft measurements by reaching close enough even in challenging environments like nighttime and in presence of obstacles. This involves developing the solution for path planning to perform flight operation autonomously, developing guidance and control algorithm for the flight operation to enable the multi-rotor to follow the designated path and perform the inspection while avoiding all the hurdles using collision avoidance system. Along with developing the specifications for a multi-rotor that can perform the inspection and suggest necessary system components including multi-rotor itself and additional components such as sensors, lights and camera, and necessities for on-board data handling.